Overexpression of microRNA-211 in Functional Dyspepsia via Downregulation of the Glial Cell Line-Derived Neurotrophic Factor (GDNF) by Increasing Phosphorylation of p38 MAPK Pathway - Jue Wang; Sai Gu; Bo Qin (Canadian Journal of Gastroenterology and Hepatology)
Background. Overexpression of miRNA-211 suppresses the differentiation of bone marrow stem cells into intestinal ganglion cells via downregulation of GDNF, a regulator of intestine barrier function. The study aimed to investigate the interaction between miR-211 and GDNF on intestinal epithelial cells. Methods. The expression levels of miR-211 and GDNF in duodenal biopsy specimens from FD patients and healthy controls were compared. Enteric glia cell (EGCs) cell line transfected with miR-211 mimics and inhibitors were used to clarify the expression levels of GDNF were analyzed by qRT-PCR and ELISA. Intestine epithelial cell (IECs) cell line cultured in medium from ECGs in different transfection conditions were used in wound healing assay, cell proliferation assay, and western blotting for evaluation of p38 MAPK phosphorylation level. Results. MiR-211 expression was significantly upregulated in the duodenal tissue of patients with FD compared to healthy subjects, whereas GDNF expression was significantly downregulated (both p<0.05). Transfection with miR-211 mimics significantly decreased GDNF mRNA expression and protein secretion (p<0.001). An inhibited intestinal epithelial cell wound healing (p<0.05) and increased expression levels of phosphorylated p38 MAPK (p<0.05) were found in IECs cultured with medium from EGCs transfected with miR-211 mimics. Conclusions. MiR-211 may downregulates GDNF mRNA and protein expression via activation of the pp38 MAPK signaling pathway. Targeting miR-211 or the MAPK pathway may be a potential intervention for FD.